2011
DOI: 10.1103/physreva.84.022342
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Dolinar receiver through multiple-copy state discrimination theory

Abstract: We consider the problem of discriminating between two quantum coherent states by interpreting a single state like being a collection of several successive copies of weaker coherent states. By means of recent results on multiple-copy state discrimination, it is possible to give a reinterpretation of the Dolinar receiver, and carry out a quite straightforward analysis of its behavior. We also propose and investigate a suboptimal detection scheme derived from the Dolinar's architecture, which is shown to slightly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 10 publications
0
54
0
Order By: Relevance
“…However, Acin et al [9] have shown that the optimum can be achieved by adaptive local measurements on the single copies, each one taking into account the results of the previous measurements (for greater details see [10]). Confining ourselves to the case n = 2, assume that the optimum measurement has been performed on the first state with correct decision probability P (…”
Section: Dolinar's Receivermentioning
confidence: 98%
“…However, Acin et al [9] have shown that the optimum can be achieved by adaptive local measurements on the single copies, each one taking into account the results of the previous measurements (for greater details see [10]). Confining ourselves to the case n = 2, assume that the optimum measurement has been performed on the first state with correct decision probability P (…”
Section: Dolinar's Receivermentioning
confidence: 98%
“…However, it is one of the innermost consequences of the laws of quantum mechanics that nonorthogonal states cannot be discriminated with certainty. Optimal detection strategies were first investigated by Helstrom [20,21] and Holevo [22] and a lot of attention has since been devoted to the development of optimal and near-optimal receivers for binary coherent states [23][24][25][26][27][28][29][30][31][32] and for the discrimination of larger signal alphabets [33][34][35][36][37][38][39][40][41]. An overview over different receiver schemes is provided in Appendix B.…”
Section: Binary Coherent-state Cloningmentioning
confidence: 99%
“…For k = 0, we initialize the process using the given priors inh k = arg max j (π j ). The prior probabilities for target absence and presence based on all measurement outcomes up to and including those from the kth cycle are given by the Bayesian update rule [17,22],…”
Section: The Ff-sfg Receivermentioning
confidence: 99%